ANALISA MANFAAT PENERAPAN E-COMMERCE PADA PERUSAHAAN RITEL - Fernando B. Siahaan (Paradigma, 2011)
Currently the competition that occurs particularly in retail sales is quite high, is marked with the number of stores popping or companies selling similar goods. This will certainly affect the number of opinions that will be obtained by each store or company. High competition is certainly going to result in two risk of profit (profit) or loss, if the profit will certainly survive, but if the loss it will be out of business, aka bankrupt. For the second risk is loss of course all companies do not want it, then how to survive and be able to generate profit? This is certainly needed a sales strategy that is right and healthy. One way is to implement e-commerce in marketing the goods or products a company has, so the purpose of this research is to benefit from the implementation of e-commerce in retail establishments. In this research used qualitative methods is to perform an in-depth interviews of business actors in the market and sell their wares. The results of this study was an increase of the number of customers on the company, and increased corporate profits. The conclusion was that implementation of e-commerce on the company's strategy to gain a competitive advantage where the company remained in existence until today. Keywords: e-commerce, customer, bisnis strategic